2020
DOI: 10.3390/molecules25173908
|View full text |Cite
|
Sign up to set email alerts
|

Isoliquiritigenin Derivatives Inhibit RANKL-Induced Osteoclastogenesis by Regulating p38 and NF-κB Activation in RAW 264.7 Cells

Abstract: Bone diseases may not be imminently life-threatening or a leading cause of death such as heart diseases or cancers. However, as aging population grows in almost every part of the world, they surely impose significant socioeconomic burden on the society, not to mention the patients and their families. Osteoporosis is the most common type of bone disease, which frequently develops in seniors, especially in postmenopausal women. Although currently several anti-osteoclastic drugs designed to suppress excessive ost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…High‐fat diet normally leads to NAFLD, but without inducing too much inflammation or fibrosis in mice models. And ISO has been reported can Improves inflammatory response (Jeong et al, 2020; Jin et al, 2019). Therefore, to analyze whether ISO would also alleviate NASH phenotype in animal models, we evaluated the role of ISO in MCD‐induced NASH model.…”
Section: Resultsmentioning
confidence: 99%
“…High‐fat diet normally leads to NAFLD, but without inducing too much inflammation or fibrosis in mice models. And ISO has been reported can Improves inflammatory response (Jeong et al, 2020; Jin et al, 2019). Therefore, to analyze whether ISO would also alleviate NASH phenotype in animal models, we evaluated the role of ISO in MCD‐induced NASH model.…”
Section: Resultsmentioning
confidence: 99%
“…ISL-derived new compounds offer another solution to improve the bioavailability and water-soluble issues [ 31 , 32 , 33 , 34 , 35 , 36 ]. Considering the chalone structure, the α,β-unsaturated ketone is an important part of its biological activity by modifying on the phenol ring to improve the performance of ISL.…”
Section: Isl’s Metabolites Pharmakinetics and Pharmacological Efmentioning
confidence: 99%
“… Synthetic isoliquiritigenin derivatives (BS5 and BS11 in Figure 2 b,c): The compounds BS5 and BS11 with m-, p-dimethoxy, o-bromo phenyl group shows neuroprotective effects at 3 μM to 6 μM with higher viability (~80–100%) [ 36 ]. Robtein (ISL-derivative #10; Figure 2 d): Robtein exhibited osteoclast differentiation and activation without any significant changes of viability or cytotoxicity [ 34 ]. 2′,4′-dimethoxy-4-hydroxychalcone ( Figure 2 e): shows in vivo antidiabetic activity [ 35 ].…”
Section: Isl’s Metabolites Pharmakinetics and Pharmacological Efmentioning
confidence: 99%
See 1 more Smart Citation
“…Engagingly, those signal ways are also targeted in the protection of diabetic myocardial dysfunction (Table 1), which naturally evokes reflections about whether a drug can work on the Nrf2/ARE pathway as well exert an antioxidant effect to inhibit ferroptosis in osteoporosis. Compounds such as luteolin (Jing et al, 2019), isoliquiritigenin (Jeong et al, 2020), and myricitrin (Huang et al, 2014) may play a corresponding role as andrographolide, which may promote or inhibit ferroptosis in osteoclasts and osteoblasts alike. Remarkably, Ma H. et al (2020) first reported that melatonin is capable of restraining ferroptosis in T2DM-induced osteoporosis, mainly by accelerating the Nrf2/HO-1 pathway, and provided convincing evidence to motivate extensive work to be done in the future.…”
Section: Ferroptosis and Osteoporosismentioning
confidence: 99%